2021
DOI: 10.1111/ajd.13547
|View full text |Cite
|
Sign up to set email alerts
|

Tissue eosinophil levels as a marker of disease severity in bullous pemphigoid

Abstract: Background: Eosinophils play an important role in bullous pemphigoid (BP) pathogenesis. Although tissue infiltration with eosinophils has been known for a long time, there is a lack of knowledge about the relationship between tissue eosinophil levels and disease severity and clinical characteristics of the patients.Methods: Fifty-nine patients diagnosed with BP between January 2008 and December 2018 were reviewed. Haematoxylin-Eosin (H&E)-stained preparations were re-evaluated in terms of tissue eosinophil lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
2
9
1
Order By: Relevance
“…Neurological diseases were significantly more common in patients with BP with high levels of eosinophils in the tissue. This finding is consistent with the results of a recent study by Karaali et al ( 21 ), which demonstrated a correlation between patients with BP with neurological disease and high tissue eosinophil counts. The study suggested that eosinophils may have a common role in the pathogenesis of BP and neurological diseases; however, further studies are needed to prove this theory ( 21 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Neurological diseases were significantly more common in patients with BP with high levels of eosinophils in the tissue. This finding is consistent with the results of a recent study by Karaali et al ( 21 ), which demonstrated a correlation between patients with BP with neurological disease and high tissue eosinophil counts. The study suggested that eosinophils may have a common role in the pathogenesis of BP and neurological diseases; however, further studies are needed to prove this theory ( 21 ).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with the results of a recent study by Karaali et al ( 21 ), which demonstrated a correlation between patients with BP with neurological disease and high tissue eosinophil counts. The study suggested that eosinophils may have a common role in the pathogenesis of BP and neurological diseases; however, further studies are needed to prove this theory ( 21 ). No differences were found in the prevalence of other comorbidities, including cardiac disease, diabetes, malignancy, and autoimmunity.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…One study found a positive correlation between tissue eosinophil level and the quantity of inflammatory lesions ( 26 ). However, with regards to the relationship between blood eosinophil count and severity of BP measured by the Bullous Pemphigoid Disease Activity Index scores, confounding data exists ( 10 , 27 29 ).…”
Section: The Role Of Eosinophils In Bullous Pemphigoid and Treatment ...mentioning
confidence: 99%